2014
DOI: 10.1111/bju.12590
|View full text |Cite
|
Sign up to set email alerts
|

Ertapenem prophylaxis reduces sepsis after transrectal biopsy of the prostate

Abstract: ObjectiveTo prospectively trial ertapenem prophylaxis in patients with known risk factors of sepsis undergoing transrectal biopsy of the prostate. Patients and MethodsIn this prospective audit, patients were identified as having a low-or high-risk of sepsis based on a questionnaire about established risk factors: previous biopsy; recurrent urine infections; receiving ciprofloxacin in the 12 months prior; travel to South-East Asia or South America in the previous 6 months; or diabetes, immune system impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Changing prophylactic antibiotic from FQ to some alternatives with low resistance rates in the rectal flora or extended antibiotic prophylaxis eliminates the need for rectal swab culture. Several studies using prophylactic antibiotics with amikacin, carbapenems and fosfomycin reported its successful use to reduce postbiopsy infectious complications …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing prophylactic antibiotic from FQ to some alternatives with low resistance rates in the rectal flora or extended antibiotic prophylaxis eliminates the need for rectal swab culture. Several studies using prophylactic antibiotics with amikacin, carbapenems and fosfomycin reported its successful use to reduce postbiopsy infectious complications …”
Section: Discussionmentioning
confidence: 99%
“…Several studies using prophylactic antibiotics with amikacin, carbapenems and fosfomycin reported its successful use to reduce postbiopsy infectious complications. [22][23][24] In addition to changing prophylactic antibiotics, several strategies have been suggested to reduce postbiopsy infectious complications. One such practice is rectal cleansing with enema, which could also improve ultrasonographic visualization of the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in this study received 1 g of intravenous ertapenem antibiotic prophylaxis as per the protocol at Wellington Hospital previously published. 17 PNB has no effect on pain from initial probe insertion into the rectum, which occurs prior to local anaesthetic infiltration. This has led to other authors investigating additional analgesic methods such as penthrox prior to probe insertion.…”
Section: Discussionmentioning
confidence: 94%
“…This may be a confounding factor and is a limitation of this study. All patients in this study received 1 g of intravenous ertapenem antibiotic prophylaxis as per the protocol at Wellington Hospital previously published …”
Section: Discussionmentioning
confidence: 99%
“…Its in vitro activity includes coverage against Enterobacteriaceae that produce extended spectrum beta-lactamases (ESBLs), and fluoroquinolone resistant E. coli, organisms that are relatively common in this patient population [18,19]. Ertapenem has been used successfully for surgical prophylaxis in non-neutropenic cancer patients undergoing procedures such as intra-abdominal surgery, colo-rectal surgery, and transrectal biopsy of the prostate [20,22]. Our current study found that at our Comprehensive Cancer Center, ertapenem is being utilized for a number of indications other than surgical prophylaxis.…”
Section: Discussionmentioning
confidence: 99%